THE ROLE OF AUDIT COMMITTEE IN CORPORATE SUSTAINABILITY DISCLOSURE - Khoiriyah, Mayla; Zarefar, Arumega; Afifah, Ulfa; Oktari, Vera (Faculty of Economics and Business University of Mataram, 2022)
This study aims to determine the influence of the characteristics of the audit committee on corporate social responsibility (CSR) disclosures as a corporate sustainability issue. The audit committee characteristics are proxied by size, the number of members with financial expertise, and the number of audit committee meetings. This study used secondary data from the annual report and sustainability report of manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2018. The number of samples used is 77 companies. Data were analyzed using Ordinary Least Square. Based on the research findings, the size of the audit committee has a significant positive effect on CSR disclosures. In contrast, financial expertise and the number of meetings significantly negatively affect CSR disclosures. This research is expected to provide recommendations to consider the size of the audit committee in establishing an audit committee to encourage broader CSR